(Poly)phenol toxicity in vivo following oral administration: A targeted narrative review of (poly)phenols from green tea, grape, and anthocyanin‐rich extracts. (2nd November 2021) - Cladis, Dennis P.; Weaver, Connie M.; Ferruzzi, Mario G.
Abstract : Fruit‐ and vegetable‐derived (poly)phenols are secondary plant metabolites that may have beneficial effects on human health when consumed regularly. Recent years have seen rapid growth in both consumer demand for and research interest in (poly)phenol‐rich dietary supplements, natural colorants, and functional foods. As these products continue to enter the marketplace and (poly)phenol intake patterns change from traditional food products to these sources, attention must be paid to the potential for toxicity from consuming elevated doses of (poly)phenols. To date, much remains unknown regarding the safety of high doses of (poly)phenols, especially in vivo . In this targeted narrative review, we summarize evidence from in vivo investigations of (poly)phenol toxicity after oral administration of green tea extracts, grape‐derived phenolics, and anthocyanin‐rich extracts. There is limited evidence of overt toxicity from oral ingestion of these (poly)phenol‐rich sources, though more research on the safety of high doses—as well as defining what constitutes a "high" dose of both individual and complex mixtures of (poly)phenols—is needed before these observations can be used to create dietary guidance for consumers.